Comparative outcomes of total arch versus hemiarch repair in acute DeBakey type I aortic dissection: the impact of 21 years of experience. (21st April 2021) - Ok, You Jung; Kang, Seung Ri; Kim, Ho Jin; Kim, Joon Bum; Choo, Suk Jung
Abstract:  : OBJECTIVES: With the goal of evaluating the impact of experiences at our centre on comparative outcomes between total arch and hemiarch repairs, we reviewed our 21 years of experience with operations for acute type I aortic dissection. METHODS: Between 1999 and 2019, a total of 365 patients (177 women; 56.8 ± 12.9 years) with acute type I aortic dissection who had a hemiarch ( n  = 248) or a total arch replacement ( n  = 117) were evaluated, and the trends in comparative outcomes were analysed. RESULTS: Over time, deep hypothermic circulatory arrest and retrograde cerebral perfusion were replaced by moderate hypothermia and antegrade cerebral perfusion with the introduction of dedicated aortic surgeons. Overall, operative deaths decreased from 11.0% in time quartile 1 to 2.2% in time quartile 4 ( P  = 0.090). After adjustment with the use of inverse probability weighting, the total arch group compared with the hemiarch group was at a similar risk of mortality [odds ratio (OR) 0.80, 95% confidence interval (CI) 0.22–2.43; P  = 0.71] but at a greater risk of neurological deficit (OR 3.28, 95% CI 1.23–8.98; P  = 0.017) in the earlier half period (1999–2009). In the later period (2009–2019), however, both the risks of mortality (OR 0.32, 95% CI 0.03–1.59; P  = 0.23) and of neurological injuries (OR 0.42, 95% CI 0.12–1.18; P  = 0.13) were comparable between the 2 groups ( P for interaction in terms of neurological deficit = 0.007). The multivariable logistic regression model revealed that dedicated aortic surgeons independently contributed to decreased risk of death (OR 0.30, 95% CI 0.09–0.84; P  = 0.036). CONCLUSIONS: These findings indicate that accumulating institutional experiences, along with resultant improvements in surgical strategies and outcomes, may neutralize the surgical risk gap between total arch and hemiarch repair in acute type I aortic dissection.